MOŻLIWOŚCI ABSORPCJI FUNDUSZY UNII EUROPEJSKIEJ PRZEZ POLSKIE REGIONY - Słodowa-Hełpa, Małgorzata (Wydział Prawa i Administracji UAM, 2005)
It is, naturally, still premature to fully assess the scale of the EU financial aid in 2004-2006, or the fund transfer, structure and the impact upon the Polish beneficiaries, as well as the causes of any possible impediments. The events of the recent months and weeks regarding the application acceptance and qualification, mainly within the ZPORR (Integrated Operational Plan for Regional Development) have given rise to numerous questions, many of which cannot yet be answered. This is because, on the one hand, the main concerns about lacking projects have been dispersed, since local governments have overwhelmed provincial authorities with applications whose value by far exceeds the available funds. On the other hand, many procedural shortcomings have been revealed, which due to the need to accelerate the work on the 2007-2013 National Development Plan and the expected decentralization of the fund implementation system in this period, in addition to the expected major increase of the available funds, all call for answers to a number of doubts regarding the methods of aid allocation and use. The article offers an evaluation of the experience gathered so far by Polish local and regional communities. This analysis is carried out in the background of the main elements determining the EU fund absorption by Polish local authorities, as well as the present system of their implementation, the respective modifications planned for 2007-2013, the scale of the aid offered and the current data on the applications filed.
POSSIBILITIES OF EU FUNDS IN POLISH REGIONS